Faculty Adoption of Teaching and Learning Technologies: Contrasting Earlier Adopters and Mainstream Faculty - Anderson, Terry; Varnhagen, Stanley; Campbell, Katy (Canadian Journal of Higher Education, 2017)
The adoption of teaching and learning technologies is an innovation that challenges the structure, culture and practice of modern research universities. This paper documents quantitatively and qualitatively the attitudes, skills and behavior of the faculty related to the use of instructional technology at a large Canadian research university. The data was gathered from a survey (n = 557) of teaching faculty. The data is analyzed with respect to Roger's (1995) categories of adoption of innovation differentiating "Earlier Adopters" (EAs) from "Mainstream Faculty" (MF). The paper discusses four factors that have tended to create a "chasm" between these two groups and discusses strategies for reducing the chasm and providing support and incentive for all faculty in the adoption of instructional technologies.